On Isotopes of Groups. III - Sokhats’kyi, F. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We describe normal congruences of group isotopes, establish criteria of homomorphism and isomorphism, and select the methods for description of isotopes up to isomorphism. In addition, we establish a criterion for a subset to be a subquasigroup of a group isotope and describe subquasigroups of certain classes of group isotopes. The obtained results are applied to the investigation of left distributive quasi-groups.